Proximal Over-Resection During Femoral Osteochondroplasty Negatively Affects the Distractive Stability of the Hip Joint. Issue 7 (31st July 2020) - Lim, Daniel; Nelson, Trevor; Eberlein, Samuel; Banffy, Michael; Metzger, Melodie; Lazaro, Lionel
Objectives: Hip microinstability is an increasingly recognized source of hip pain and disability. Femoral osteochondroplasty is usually performed with direct visualization through the arthroscope, assisted with repeated fluoroscopic view for orientation and feedback. However, a two-dimensional representation of a three dimensional structure can be misleading compromising the precision of the planned osteochondroplasty. Sometimes the resection can extend proximally into the Femoral Head (FH) diminishing the surface area of the articular cartilage available to be in contact with the labrum, in order to create the suction effect (suction seal) that maintains the stability of the femoral head in the acetabulum. The purpose of the study is to evaluate the role of proximal over-resection of femoral osteochondroplasty in the rotational and distractive stability of the hip joint. We hypothesis that proximal over resection will result in decrease stability, specially at higher degrees of flexion and internal rotation where the contact between labrum and articular cartilage will be lost, and breaking the suction seal. Methods: Six hemi-pelvises were repeatedly tested in the following five conditions: (a) intact, (b) T-capsulotomy, (c) Osteochondroplasty to the level of the physeal scar, followed by a (d) 5mm and (e) 10mm proximal extension of the resection. The pelvis was secured to a metal plate and the distal portion of the femur was potted and attached to a multi-axial hip jig. (Fig.1) Specimens were axially distracted with a load from 0-150N followed by 5Nm of internal and external torque at 0 o, 15 o, 30 o, 60 o, 90o of flexion while the resultant displacement/rotation was recorded using a 3D motion tracking system. Repeated measures ANOVA was used with statistical significance set at p<0.05. Results: Proximal extension of the resection by 5mm and 10mm increased axial instability (decreased force required for hip distraction) at every angle of flexion tested, with the greatest increase observed at higher angles of flexion (60 deg and 90 deg), p<0.05. T-capsulotomy alone increased both internal and external rotation at all angles of flexion, p<0.05. (Fig. 2) Subsequent resection and extension of the resection did not significantly increase rotational instability compared to the capsulotomy state. Conclusion: Extending the osteochondroplasty proximally into the femoral head compromised the distractive stability of the hip joint. It is important to be precise when performing femoral osteochondroplasty to minimize proximal extension that can lead to iatrogenic instability of the hip joint and poor postoperative outcomes. Figure 1. Figure 2.